1980
DOI: 10.1128/jb.144.1.185-191.1980
|View full text |Cite
|
Sign up to set email alerts
|

Further characterization of sfiA and sfiB mutations in Escherichia coli

Abstract: The sfiA and sfiB mutations, originally isolated in thermoresistant ultraviolet-resistant revertants of a tif lon strain, also suppressed filamentation in tsl strains (mutated at the lexA locus). When deoxyribonucleic acid synthesis was arrested, however, sfi-independent filamentation occurred. Other SOS functions were not affected by sfiA and sfiB mutations; in particular, ultraviolet-induced repair and mutagenesis of bacterial deoxyribonucleic acid were normal, as was tsl-tif-induced synthesis of recA protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 14 publications
(20 reference statements)
7
26
0
Order By: Relevance
“…Finally, some comment is required on the previously reported recessivity of sjiBl 14 and other sfj1B alleles. In the case of sf11B1 14, the presence of a recessive allele in partial diploids appeared to be demonstrated unequivocally by subsequent P1 transduction analysis (Huisman et al, 1980c). Nevertheless, both in this study and that recently reported by Lutkenhaus (1983), sf1B (suiB) alleles were clearly shown to be dominant.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Finally, some comment is required on the previously reported recessivity of sjiBl 14 and other sfj1B alleles. In the case of sf11B1 14, the presence of a recessive allele in partial diploids appeared to be demonstrated unequivocally by subsequent P1 transduction analysis (Huisman et al, 1980c). Nevertheless, both in this study and that recently reported by Lutkenhaus (1983), sf1B (suiB) alleles were clearly shown to be dominant.…”
Section: Discussionsupporting
confidence: 57%
“…Similar results are obtained with mutations, (tij), in recA which lead to activation of the protease form of the recA protein at 42°C, and consequent cleavage of the lexA repressor (Little et al, 1980). Mutations in sflA and a second locus sfiB suppress filament formation in both tsl and tif mutants at 42°C (Witkin, 1976;Huisman et al, 1980bHuisman et al, , 1980c. Similarly, mutations in another gene, Ion, which block or delay recovery from u.v.induced division inhibition are also suppressed by sflA (sulA) and sJfB (suiB) mutations (George et al, 1975;Johnson, 1977;Gottesman et al, 1981).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…It is known that cell division arrest induced during DNA damage is mediated by the binding of FtsZ by SulA protein in order to prevent FtsZ-ring assembly (Huang et al 1996, Higashitani et al 1997, Mukherjee et al 1998, Trusca et al 1998, Justice et al 2000, Cordell et al 2003, Kawai et al 2003, thereby leaving FtsZ unutilized. In a similar manner, it is possible that FtsH might degrade unutilized FtsZ if septation arrest is induced by DNA replication inhibition (Huisman et al 1980, 1984, Huisman and D'Ari, 1981. AR5090/pSTD113 cultures were induced for FtsH expression for 60 min, and then treated with the DNA replication inhibitors, hydroxyurea, nalidixic acid, phenethylalcohol or mitomycin C at the final concentrations of 66 mM (Sinha and Snustad 1972) or 20 µg/ml (Goss et al 1965) or 0.4% (Kaneko et al 1977) or 3 µg/ml (Khil and Camerini-Otero 2002), respectively, for further 60 min.…”
Section: Ftsh Does Not Degrade Ftsz Even Under Cell Division Arrestedmentioning
confidence: 99%
“…These tif Ion strains filament extensively at a high temperature; the sfi survivors show less filamentation. We will assume in our discussion that the sulA and sfiA mutations are allelic and that sulB and sfiB are allelic, since their phenotypes are indistinguishable and they map in the same regions of the chromosome (6,12,13,14).…”
mentioning
confidence: 99%